Analisis Pengaruh Gaya Mengajar Guru terhadap Pembentukan Karakter Siswa di Lingkungan Sekolah - Anisa Putri Melinda Djo; Yakobus Adi Saingo (Jurnal Pendidikan Agama dan Teologi, 2026)
This study aims to analyze the influence of teachers' teaching styles on the formation of student character in the school environment. The study focuses on comparing democratic-humanist and authoritarian teaching styles, and their implications for student character development. The research method used is a qualitative method with a literature review approach, through a systematic analysis of books, scientific articles, and previous research results relevant to the topic of teaching styles and character education. The results and discussion indicate that education is not only oriented towards academic achievement, but also on the formation of moral values, attitudes, and personality of students. Teachers have a strategic role as educators, mentors, and role models whose behavior and teaching styles greatly influence student character. Democratic and humanist teaching styles have been shown to encourage the growth of self-confidence, courage to express opinions, independence, empathy, and moral integrity in students. Conversely, authoritarian teaching styles tend to instill fear, reduce creativity, weaken self-confidence, and shape students' character under pressure. This study confirms that student character formation is strongly influenced by the quality of teacher-student interactions, the emotional atmosphere in the classroom, role models, and moral communication established by teachers. Therefore, a balance is needed in implementing a firm but humanistic teaching style in order to create a learning environment that is conducive to optimal character formation of students.